The MIGRATION AS AN INVASION and THE COMMON EUROPEAN HOUSE Metaphors in media discourse - Mujagić, Mersina (ExELL, 2025)
The article discusses figurative use of expressions from the domains of INVASION and HOUSE in media discourse on the European migrant crisis. The conceptual metaphors MI-GRATION AS AN INVASION and the COMMON EUROPEAN HOUSE, which are inextricably relat-ed in the segments of the real discourse on migration, have strong rhetorical power and serve as a means of promoting antimigrant ideologies. The aim of this paper is to identify the instances of deliberate use of the aforementioned metaphors in British and Bosnian-Herzegovinian papers and describe their use in the media with the aim of changing address-ees’ perspectives on an important issue such as migration.